BIRD’S NEST EXTRACT CREAM: TREATMENT FOR PERINEAL WOUND IN RATTUS NORVEGICUS - Herlina Ofiwijayanti; Syarief Thaufik Hidayat; Nur Khafidhoh (Belitung Raya Foundation, Indonesia, 2017)
Background: Perineal rupture occurs almost in all the first labor and not infrequently in the next labor. Complex perineal wounds are at risk for non-healing and infection. Objective: This study aims to determine the effect of bird’s nest extract on perineal wound healing on rattus norvegicus. Methods: This was a randomized posttest only group design conducted in October 2016 at Animal Laboratory Unit of Diponegoro University, Semarang, Indonesia. There were 30 samples recruited in this study, divided into three groups: 1) the control group (with povidone iodine 10% solution), 2) the first treatment group with a bird’s nest 50% cream, and 3) the second treatment group with a bird’s nest 70% cream. The Redness, Edema, Ecchymosis, Discharge, Approximation (REEDA) scale was used. Data were analyzed using descriptive statistics, frequency distribution, and one-way ANOVA. Results: There were statistically significant mean differences between the three groups with p-value 0.000 (< 0.05). The time of the wound healing was 5-6 days for povidone iodine 10% group, 4-5 days for bird’s nest 50% group, and 3 days for bird’s nest 70% group. The degree of perineal wound density in the bird’s nest 70% group (0.37) was also better than the bird’s nest 50% group (0.13) and povidone iodine 10% group (0.02). Conclusion: Bird’s nest has a significant effect on wound healing process. Findings indicated that the bird’s nest 70% extract was very effective to accelerate wound healing than bird’s nest 50% extract and povidone iodine 10%.